Studi Pengukuran Tahanan Pentanahan Tower Saluran Udara Tegangan Exstra Tinggi (SUTET) 500 KV Pedan-Ungaran - Farmada, Andre; , Ir. Jatmiko, M.T (2016)
PT PLN (Persero) Salatiga Basecamp is a power company engaged in the maintenance and repair of electricity in Central Java. One of the areas of maintenance and repair of basecamp Salatiga is extra high-voltage air transmission line tower (SUTET) 500 kV Pedan-Ungaran. In the process of repair and maintenance, often found a power outage caused by overcurrent or overvoltage. This is certainly very dangerous for equipments, humans, or other living creatures. To overcome that things, it is made a grounding path that is a grounding electrode implanted into the ground. The existence of this grounding system makes the fault current can be quickly drained into the ground and spread in all directions. The size of the value of the grounding is strongly influenced by the composition of the soil around the tower and conductive electrode implanted. The smaller the value of grounding resistance, the faster it will be drained into the earth. Grounding value of tower can be known by do the measurement of grounding value. The maximum value allowed by PT PLN (Persero) SUTET 500 kV transmission lines of 15 Ω. Transmission line tower of Pedan-Ungaran has as many as 174 types of electrodes can be called a grounding rod. The number of electrodes implanted into the soil are four electrodes installed in parallel. The combined measurement of four electrodes implanted in 3 meters deep has a resistance value of 2 Ω. This value can be minimized by proving that is grounding resistance calculation analysis by replacing the custody grounding electrode rod as deep as 4 meters gotten the grounding resistance values of 1.56 Ω or use electrode rod with a depth of 5 meters which can grounding resistance values of 1.29 Ω.